2002
DOI: 10.1677/joe.0.1730013
|View full text |Cite
|
Sign up to set email alerts
|

Gap junction proteins and cell-cell communication in the three functional zones of the adrenal gland

Abstract: Mouse and monkey adrenal glands were used to study the relationships between gap junction protein expression, intercellular communication and adrenal zonation. Dye communication patterns were determined by incubating freshly excised and hemisected adrenal glands in Lucifer yellow, a gap junction permeable fluorescent dye. Immunohistochemical techniques were used to localize adrenal gap junction proteins. The combination of these two techniques permitted the correlation of gap junction proteins with dye transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Gap junctions were shown to be abundant in the zonae fasciculata (ZF) and reticularis (ZR) of the adrenal gland cortex; however, only a few plaques were found in cells of the zona glomerulosa (ZG). Immunohistochemical analysis demonstrated Cx43 as the major connexin expressed in the cortex of the adrenal gland (Murray and Pharrams, 1997;Davis et al, 2002). Martin et al (2001) showed by RT-PCR analysis that neural crest cell-derived chromaffin cells coexpressed Cx36 and, contrary to other results (see above), Cx43.…”
Section: Cx36 Expression Outside the Cnsmentioning
confidence: 81%
“…Gap junctions were shown to be abundant in the zonae fasciculata (ZF) and reticularis (ZR) of the adrenal gland cortex; however, only a few plaques were found in cells of the zona glomerulosa (ZG). Immunohistochemical analysis demonstrated Cx43 as the major connexin expressed in the cortex of the adrenal gland (Murray and Pharrams, 1997;Davis et al, 2002). Martin et al (2001) showed by RT-PCR analysis that neural crest cell-derived chromaffin cells coexpressed Cx36 and, contrary to other results (see above), Cx43.…”
Section: Cx36 Expression Outside the Cnsmentioning
confidence: 81%
“…Of note, we recently identified Cx37, Cx40 and Cx45 transcripts in the mouse cortex (unpublished results). Abundant Cx43-built gap junction plaques are present in the ZF and ZR, while cells within the ZG exhibit few, if any, gap junctions [8,9,13,14] (Table 2). Single cell reverse transcriptase polymerase chain reaction analysis experiments have also revealed the presence of Cx43 mRNA in the ZF and ZR [15].…”
Section: Connexin Expression and Distributionmentioning
confidence: 99%
“…As hypothesized [21], gap junctional communication in the adrenal cortex plays a pivotal role in a number of interactive cell [8,9,13,15] Mouse ? [9,12,14,27] Guinea pig ? [9] Cow ?…”
Section: Connexin Intercellular Channelsmentioning
confidence: 99%
“…The endocrine cells of the adrenal cortex are coupled by Cx43 channels (343,368,370), particularly in the glucocorticoid-and the androgen-producing regions (107). In vitro experiments testing drugs thought to block Cx43 channels have documented an impaired secretion of cortisol from clusters of adrenal cells, but not single cells, stimulated by ACTH but not cAMP (366).…”
Section: Steroid-producing Endocrinesmentioning
confidence: 99%